The Association of Internet Addiction Disorder with Personality Type and Parenting Style among High School Students in Jahrom, Southern Iran - Yaser Sarikhani; Mohammad Rafiee; Tahereh Ostovar (Shiraz University of Medical Sciences, 2021)
Background: Internet addiction disorder (IAD) has become a major global issue in the modern society. Adolescents may be more prone to IAD due to their particular conditions. The current study aimed to investigate the association of IAD with personality types and parenting styles among a sample of Iranian high school students. Methods: In this cross-sectional study, 400 students (50% male), with a mean age of 15.5±1.7 years, were selected randomly from the high schools in Jahrom city, Fars Province of Iran, in 2020. In addition to the demographic information, each participant was asked to fill out three standard questionnaires concerning IAD, parenting style, and personality types. Logistic regression was used to measure the odds ratio and there was a 95% confidence interval regarding the relationship between the independent variables and IAD. The data were analyzed with SPSS version 17. Results: According to the results of the study, 25.5% of the students had severe IAD. The results of the backward logistic regression showed that the adolescents whose fathers (OR: 13.39, CI: 5.34-23.56) and mothers (OR: 13.64, CI: 7.89-24.99) had a permissive parenting style, as well as those with the personality types of psychoticism (OR: 10.83, CI: 4.26-19-59) and neuroticism (OR: 20.65, CI: 10.06-34.91), were at a higher risk of IAD. Conclusion: The present study revealed that certain personality types and parenting styles are associated with an increased risk of developing IAD in adolescents. These results could be considered to develop appropriate programs for the prevention and control of the problem at the national or regional levels.